2021
DOI: 10.3390/agronomy11020204
|View full text |Cite
|
Sign up to set email alerts
|

Organic Matter Properties of Spent Button Mushroom Substrate in the Context of Soil Organic Matter Reproduction

Abstract: The objective of the work was to evaluate selected properties of spent substrates used for growing button mushrooms (SMSs) and the content and quality of the organic matter in this material in the context of rational use for fertilisation purposes and potential impact on the soil environment. The materials were sampled at production facilities located in the east of Mazovia. The density and amount of spent substrate on shelves where mushrooms were cultivated were determined. The following were analysed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…The spent mushroom substrates may enrich soils with organic matter, nitrogen, and carbonates, improving their fertility and preventing soil degradation [6]. To date, a large volume of research has indicated that soil properties-such as pH, organic carbon content, bulk density, enzymatic and microbial activity-are improved by different organic additives [37][38][39].…”
Section: Effects Of Additives On Soil Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The spent mushroom substrates may enrich soils with organic matter, nitrogen, and carbonates, improving their fertility and preventing soil degradation [6]. To date, a large volume of research has indicated that soil properties-such as pH, organic carbon content, bulk density, enzymatic and microbial activity-are improved by different organic additives [37][38][39].…”
Section: Effects Of Additives On Soil Propertiesmentioning
confidence: 99%
“…Several studies have assessed the effects of organic matter application in the long-term experiments, but with additives such as biochar, composts, sewage sludge and farmyard manure [40][41][42]. The influence of spent mushroom substrate and chicken manure on soil properties has only been tested in a few short-term experiments [3][4][5][6][7][8][9]. From a comparison of the results between the short-term and our 20-year studies, it is apparent that the positive effects of spent mushroom substrate (SMS) and chicken manure (CM) on the soil characteristics-such as the content of nutrients, water, and organic carbonwere cumulative compared to control soil (CS).…”
Section: Effects Of Additives On Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of variance confirmed that the soil sampled from the 10-20 cm layer recorded significantly lower (by 23.7%) mean values of the ratio TOC/Nt, as compared with the soil sampled from the 0-10 cm layer (p = 0.0001) (Table 2). The values of the TOC/Nt ratio for the soil sampled 10-20 cm deep can be indicative of a high degree of transformation of organic matter present in the material, and of a prevalence of mineralisation over synthesis of organic nitrogen compounds [75].…”
Section: Basic Parameters Of Soilsmentioning
confidence: 99%
“…Gypsum addition significantly ameliorates the Ca 2+ and reduces the Al 3+ toxicity, while no effect has been reported on soil pH [ 16 ]. Mushroom residue is characterized by a low toxic content while having a higher content of organic matter [ 17 ]. Nevertheless, mushroom residue has also been reported to improve the soil structure, with a significant effect on improving the soil pH.…”
Section: Introductionmentioning
confidence: 99%